Multiscale additive manufacturing of polymers using 3D photo-printable self-assembling ionic liquid monomers. Issue 3 (17th April 2019) - Ndefru, Bineh G.; Ringstrand, Bryan S.; Diouf, Sokhna I.-Y.; Seifert, Sönke; Leal, Juan H.; Semelsberger, Troy A.; Dreier, Timothy A.; Firestone, Millicent A.
Abstract : Combining bottom-up self-assembly with top-down 3D photoprinting affords a low cost approach for the introduction of nanoscale features into a build with low resolution features. Abstract : 3D photoprinting of a self-assembled ionic liquid (IL) monomer based liquid-crystalline mesophase introduces high-resolution nanoscale features (2–5 nm) into otherwise low-resolution (microscale features) polymer builds. A wide variety of geometric builds possessing internal hexagonal perforated lamellar (HPL) nanostructure containing ∼2.4 nm diameter pores are fabricated by the digital light processing 3D printing of an aqueous mixture (61(w/w%)) of an ionic liquid monomer, 1-decyl-3-vinylimidazolium chloride, a co-monomer, polyethylene diacrylate (PEGDA, M n 575), and a visible light photo-initiator (eosin Y and triethanolamine). Vibrational spectroscopy and thermal analysis proves acrylate moiety polymerization occurs during printing but incomplete consumption of the IL vinyl groups. Post-printing exposure to UV light ( λ 350 nm) completes vinyl polymerization serving to further improve nanostructure ordering as determined by SAXS. Solvent swelling (ethanol) induces a structural transformation to a body center cubic architecture accompanied by slight pore expansion (to 3.2 nm). The introduction of nanoscale features into low-resolution photo-printed polymers establishes a low-cost strategy for the additive manufacturing of multi-scale, structured nanoporous polymer membranes.